Introducing Pediatric Radiology as a subspecialty in Pakistan: Bridging the Gap in Healthcare - Hameed, Marya; Siddiqui, Fatima; Shaikh, Fahad Hassan (Journal of the Pakistan Medical Association, 2023)
Madam, Radiology is a rapidly progressing field that significantly contributes to disease diagnosis and treatment monitoring. Recent advancements in the field have improved evidence-based medicine for patient care. Despite substantial growth in Pakistan, limited opportunities for sub-specialisation training in radiology are available in Pakistan. Just a few institutions offer training in sub-specialties such as women’s imaging, neurologic radiology, interventional radiology, and body imaging. There has been significant evolution in pediatric radiology, which has now emerged as a distinct field requiring solid foundations. Unfortunately, due to undefined training opportunities, pediatric radiology is being neglected in Pakistan. Pediatric radiology requires specialized training due to anatomical variations and unique disease presentations in children. Even senior general radiologists may lack confidence when reporting pediatric cases. Radiology demands updated knowledge and expertise in diagnostic tools, making it challenging to keep up. Reporting pitfalls in pediatrics differ from adults due to varying growth patterns and myelination making expert knowledge essential for accurate reporting in multiple conditions. The acceptable radiation doses and protocols for imaging studies are also different, considering children’s susceptibility to ionizing radiation3. The European Society of Radiology highlighted the importance of integrating pediatric radiology training4. Many other countries, including the USA and Europe, have sub-specializations and accreditations despite having lower proportions of children in their populations compared to Pakistan. Advocacy movements for pediatric radiology have also emerged in other developing nations like Nigeria5. Pakistan is a largely populated country, with approximately 35% being pediatric population and multiple radiological cases being reported daily. It seems a gross neglect not to cater specifically to such a large proportion of the people. Therefore, there is a dire need to recognize pediatric radiology as a formal subspeciality that requires redrafting of the curriculum. The subspecialty should focus on a particular area and offer comprehensive and consistent training to interested individuals.